2020
DOI: 10.1186/s42523-020-00049-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influences on oral and faecal microbiota maturation in neonatal calves in beef and dairy production systems

Abstract: Background The dam is considered an important source of microbes for the calf; consequently, the development of calf microbiota may vary with farming system due to differences between the contact the calf has with the dam. The objective of this study was to characterise the early changes in the composition of oral and faecal microbiota in beef and dairy calves (N = 10) using high-throughput sequencing of the 16S rRNA gene. The microbiota of calves was compared to selected anatomical niches on their dams which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
2
16
2
Order By: Relevance
“…However, the principal coordinate scatter plot demonstrated dam fecal samples tightly clustered while vaginal and oral samples were not. Previous literature shows similar results and provides some insight on how various maternal microbiomes are inoculated, but these results also point towards the difficulty of determining bacterial contamination versus inoculant [27,43]. The broader clustering of the vaginal and oral microbiomes makes sense, as these sites not only contain bacteria typically commensal to that location, but they are also consistently exposed to sources of new bacteria, like feed for the oral cavity or feces and bedding for the vagina, which would increase beta diversity of the microbiome [27,44].…”
Section: Variation Between Maternal Sourcessupporting
confidence: 72%
“…However, the principal coordinate scatter plot demonstrated dam fecal samples tightly clustered while vaginal and oral samples were not. Previous literature shows similar results and provides some insight on how various maternal microbiomes are inoculated, but these results also point towards the difficulty of determining bacterial contamination versus inoculant [27,43]. The broader clustering of the vaginal and oral microbiomes makes sense, as these sites not only contain bacteria typically commensal to that location, but they are also consistently exposed to sources of new bacteria, like feed for the oral cavity or feces and bedding for the vagina, which would increase beta diversity of the microbiome [27,44].…”
Section: Variation Between Maternal Sourcessupporting
confidence: 72%
“…The calves age as well as the time of weaning also affected the OS microbiota at both phylum-and genuslevel. A recent study reported that the oral microbiota of neonatal calves matured quickly and contained similar microbial composition to the adult cow oral microbiota by four-weeks of age [33]. In the present study, the oral samples were collected at seven-weeks of age, thus, it is presumable that the oral microbiota was matured and the major changes observed in OS microbiota composition were mainly caused by weaning related dietary shifts.…”
Section: Discussionmentioning
confidence: 69%
“…At the time of weaning, calves were moved to another strawbedded barn in groups of different sizes. EarlyC group was weaned at 7 weeks of age (days [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and lateC group at 17 weeks of age (days 98-112). During weaning, the amount of milk replacer was reduced in a 14 days stepdown approach from 1.35 kg/d to 0.3 kg/d.…”
Section: Animals Management and Dietsmentioning
confidence: 99%
“…Interestingly, we did not observe any bright sick beef-cross (Jersey x Angus) calves. Beef operations tend to have different management practices than dairies [ 35 ], with greater cow-calf interactions and lower human-calf handling. Therefore, it is known that different factors can influence diarrhea in dairy and beef operations.…”
Section: Discussionmentioning
confidence: 99%